2019
DOI: 10.7146/ffi.v34i1.117042
|View full text |Cite
|
Sign up to set email alerts
|

Fodbold Fitness

Abstract: I denne artikel stilles der skarpt på Fodbold Fitness. Et initiativ som Dansk Boldspil-Union (DBU) lancerer i 2011 som en reaktion på flere forskellige udviklingstendenser i det danske idrætsliv. DBU beskriver Fodbold Fitness som fodbold på en ”sportslig og organisatorisk helt ny måde, der bryder med den traditionelle organisering, administration og medlemsstruktur”. Resultaterne af analysen viser, at Fodbold Fitness bryder med fritidsfodboldens sportslige form, men ikke med den organisatoriske form. Dette udf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…As we also mentioned at the beginning of the article, initially the concept had far more appeal to women than to men. Among other things, research as well as the analysis of this article have shown that the connotations of the word fitness did not appeal as much to men as to women (Bennike, 2016; Thing and Ottesen, 2019). As such, clubs that offer this concept to men can now choose to call it Exercise football instead (Nordea-Fonden, 2015).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…As we also mentioned at the beginning of the article, initially the concept had far more appeal to women than to men. Among other things, research as well as the analysis of this article have shown that the connotations of the word fitness did not appeal as much to men as to women (Bennike, 2016; Thing and Ottesen, 2019). As such, clubs that offer this concept to men can now choose to call it Exercise football instead (Nordea-Fonden, 2015).…”
Section: Discussionmentioning
confidence: 88%
“…Some only for men or women, others for both genders (see www.bevaegdigforlivet.dk/fodbold). Overall, the concept FF has been more appealing among women than men (Bennike, 2016; Bennike et al, 2014; Thing et al, 2017, 2019), and more female teams than male teams have been established nationally. However, many male teams do exist successfully, and this article will explore what enables and restricts (Elias, 1994 [1939]) the development of FF among male players.…”
Section: Introductionmentioning
confidence: 99%